2021
DOI: 10.22541/au.162688529.91368860/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nest architecture is linked with ecological success in songbirds

Abstract: Bird nests are essential structures that directly determine the fitness of an organism. While there is theory and evidence predicting an association between species nest traits and their habitat, few studies have comprehensively examined the macroevolutionary patterns driving nest evolution, species niche and their interrelation. Using information on 3174 species of songbirds, we show that species that build domed nests (i.e. nests with a roof) have smaller ranges, narrower thermal niches, are less likely to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This comparison emphasizes that phylogenetic studies of specialization that do not account for hidden states may need to reevaluate their null hypotheses of diversification. For example, a recent study by Medina et al (2022) concluded that there are differences in extinction rates between cup and dome nesters, but hidden state models in this study were not presented due to failed convergence, and extinction rates cannot be interpreted independently from speciation rates (Helmstetter et al 2021), so the link between nest type and diversification remained untested. Our results, in combination with recent tests of the evolutionary dead end hypothesis, show that there is growing evidence that specialization rarely leads to an evolutionary dead end (Stern et al 2017; Villastrigo et al 2020).…”
Section: Discussionmentioning
confidence: 82%
“…This comparison emphasizes that phylogenetic studies of specialization that do not account for hidden states may need to reevaluate their null hypotheses of diversification. For example, a recent study by Medina et al (2022) concluded that there are differences in extinction rates between cup and dome nesters, but hidden state models in this study were not presented due to failed convergence, and extinction rates cannot be interpreted independently from speciation rates (Helmstetter et al 2021), so the link between nest type and diversification remained untested. Our results, in combination with recent tests of the evolutionary dead end hypothesis, show that there is growing evidence that specialization rarely leads to an evolutionary dead end (Stern et al 2017; Villastrigo et al 2020).…”
Section: Discussionmentioning
confidence: 82%